Toxocariasis: Serological diagnosis by indirect antibody competition elisa - Nunes, Caris Maroni [UNESP]; Tundisi, Regina Nardini; Heinemann, Marcos Bryan; Ogassawara, Saemi; Richtzenhain, Leonardo José (FapUNIFESP (SciELO), 1999)
Toxocariasis is caused by infection of man by Toxocara canis and Toxocara, cati larvae, the common roundworm of dogs and cats. Because larvae are difficult to detect in tissues, diagnosis is mostly based on serology. Non specific reactions are observed mainly due to cross-reactivity with Ascaris sp antigens. This investigation aimed at developing and evaluating an indirect antibody competition ELISA (IACE) employing a specific rabbit IgG anti-Toxocara canis excretory-secretory antigens as the competition antibody. in order to improve indirect ELISA specificity performed for toxocariasis diagnosis. For that, the rabbit IgG was previously absorbed by Ascaris suum adult antigens. Sensitivity and specificity of IACE were first evaluated in 28 serum samples of mice experimentally infected with T. canis embryonated eggs. Adopting cut-off value established in this population before infection, sensitivity and specificity were 100% after 20 days post-inoculation. For human population IACE was evaluated using sera from 440 patients with clinical signs of toxocariasis and the cut-off value was established with 60 serum samples from apparently healthy individuals. Using as reference test the indirect ELISA performed by Adolfo Lutz Institute, sensitivity was 60.2%, specificity was 98% and concordance was 77.3%. Repeatability of IACE was evaluated by the inter-reactions variation coefficient (2.4%).
Keywords: Immunodiagnosis; Indirect antibody competition ELISA; Toxocara canis; Toxocariasis; Visceral larva migrans; helminth antibody; immunoglobulin G; parasite antigen; animal; blood; enzyme linked immunosorbent assay; female; human; immunology; methodology; mouse; sensitivity and specificity; serology; toxocariasis; Animals; Antibodies, Helminth; Antigens, Helminth; Enzyme-Linked Immunosorbent Assay; Female; Humans; Immunoglobulin G; Mice; Sensitivity and Specificity; Serologic Tests